2017
DOI: 10.1101/098590
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Active diffusion and advection in theDrosophilaooplasm result from the interplay of the actin and microtubule cytoskeletons

Abstract: Transport in cells occurs via a delicate interplay of passive and active processes, including diffusion, directed transport and advection. Despite progresses in super-resolution microscopy, discriminating and quantifying these processes is a challenge, requiring tracking of rapidly moving, sub-diffraction objects in a crowded, noisy environment. Here we use Differential Dynamic Microscopy with different contrast mechanisms to provide a thorough characterization of the dynamics in the Drosophila oocyte. We stud… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…To quantify the active dynamics of myosin-driven networks, we use differential dynamic microscopy (DDM) to analyze time-series of images. DDM is useful for investigating diffusive and active dynamics of soft materials such as those found in biological systems 32 , including cytoskeleton complexes [33][34][35] . In our own previous work, we have used DDM to study the passive transport of tracers within static actin-microtubule networks, and found that these networks exhibit subdiffusive behavior 36 .…”
Section: Microtubules Slow Actomyosin Activity 7-foldmentioning
confidence: 99%
“…To quantify the active dynamics of myosin-driven networks, we use differential dynamic microscopy (DDM) to analyze time-series of images. DDM is useful for investigating diffusive and active dynamics of soft materials such as those found in biological systems 32 , including cytoskeleton complexes [33][34][35] . In our own previous work, we have used DDM to study the passive transport of tracers within static actin-microtubule networks, and found that these networks exhibit subdiffusive behavior 36 .…”
Section: Microtubules Slow Actomyosin Activity 7-foldmentioning
confidence: 99%
“…More in general, the use of different contrast mechanisms can be beneficial in probing the multi-scale dynamics in a complex environment, such as for instance the cell interior 36 . A significant step in this direction was taken by Drechsler, Giavazzi et al 37 , who combined ConDDM and Differential Interference Contrast DDM (DIC-DDM) to probe selectively inside a Drosophila oocyte the dynamics of cytoskeletal filamentous actin (F-actin) and endogenous vesicles, respectively. During oogenesis, the oocyte is characterized by a combination of different transport mechanisms, including directed transport by cytoplasmic flows 38 and active diffusion 39 .…”
Section: Anomalous Dynamics Of Intruders In a Crowded Environment mentioning
confidence: 99%
“…We expect that DDM-µr can be successfully used to measure the rheological properties of a variety of soft materials, also in cases where DLS, DWS and PT can not be used. A typical example is the cell interior [29] where DDM has already been successfully used to measure the interplay of diffusion and flow during oogenesis.…”
Section: Introductionmentioning
confidence: 99%